FESTIVAL TUMPENG SEWU SEBAGAI PEMBANGUNAN IDENTITAS SUKU OSING BAGI GENERASI MUDA DI DESA KEMIREN KECAMATAN GLAGAH KABUPATEN BANYUWANGI - Yulvinda, Rossa; Sarmini, Sarmini (Universitas Negeri Surabaya (Unesa), 2025)
Tradition plays a very significant role as a social bond and a medium for character education. Values ​​such as mutual cooperation, religiosity, tolerance, discipline, and responsibility are often reflected in various local traditions, such as Tumpeng Sewu in Banyuwangi. In its implementation, many young people still consider the tradition to be just an annual event and still lack the meaning of the existing character values. This study uses a descriptive analysis research method. Data from this study were obtained from interviews, observations and documentation. The informants in this study were the Head of Kemiren Village Customs and the Kemiren Village Community. The results of this study indicate that in the Tumpeng Sewu tradition there are two processions that are part of the tradition. The first is a series of traditional ceremonies before the Tumpeng Sewu tradition, including Mepe Kasur, Parade, Barong Kemiren and Torch Parade or Oncor, then continued with the implementation of the Tumpeng Sewu Tradition itself. Some of the meanings of the Tumpeng Sewu Tradition are as an expression of the village's gratitude to the Danyang Desa or ancestors. Then, as a symbol of brotherhood and strengthening the ties of friendship between the Kemiren community and the general public and as a symbol that the traditions of the ancestors have never been eroded by time, even though modernization is increasingly dominating at this time. The Tumpeng Sewu tradition can survive until now because the young people in Kemiren Village have a sense of caring and a very high sense of enthusiasm. This tradition will continue to exist because the tradition was born from the Kemiren community and is also one with the Kemiren community.